Isolated Systolic Hypertension in Young Adults: a Narrative Review of Epidemiology, Pathophysiology and Clinical Management - Janasik, Laura; Kociucka, Patrycja; Sadowski, Krzysztof; Modelska, Julia; Jeleń, Anita; Podolska, Anna; Paluchowicz, Karolina; Siwicka, Katarzyna; Szewczyk, Konrad (Journal of Education, Health and Sport, 2026)
Background: Isolated systolic hypertension in young adults is a problem of rising importance. Although it has been considered a benign condition caused by a hemodynamic phenomenon in a specific patient group, current population-based studies challenge this view. These data suggest increased cardiovascular risk and possible progression to sustained hypertension. Aim: The aim of this narrative review is to summarize current evidence on isolated systolic hypertension in young adults and to compare recent findings with previous studies and the concept of spurious systolic hypertension. Materials and methods: A systematic literature search using PubMed and Google Scholar online databases was conducted. Authors included and analyzed 30 studies published between 2000 and 2025 focusing on epidemiology, pathophysiology, hypertension progression, cardiovascular risk and therapeutic management of isolated systolic hypertension. Results: The prevalence of isolated systolic hypertension appears to be increasing, affecting a considerable proportion of the young adults population, especially men. Hemodynamic findings suggest heterogeneity of pathophysiological mechanisms underlying this condition, including high arterial pulse pressure amplification, elevated stroke volume and aortic stiffness. Evidence indicates possible progression to sustained hypertension and increased cardiovascular disease and mortality risk. Data regarding therapeutic management is limited with current guidelines recommending a non-pharmacological approach. Conclusions: Isolated systolic hypertension in young adults is a heterogeneous condition requiring further research to optimize its clinical management.